Experimental study on the nozzle-shape effect on liquid jet characteristics in gaseous crossflow - Jalili, B.; Jalili, P.; Ommi, F.; Ganji, D. D. (Frontiers in Mechanical Engineering, 2023)
This study presents experimental findings on the crossflow injection of a liquid jet into a gaseous flow. Crossflow injection is favored over co-axial trajectory injection because of its potential to enhance atomization, promote the formation of smaller droplets, and improve injection parameters, mainly due to the differing trajectory of fuel injection within the transverse airflow. The experiments use two circular and four elliptical nozzles with varying aspect ratios. The research investigates the influential factors affecting the trajectory and breakup of the liquid jet. Specifically, the impact of nozzle geometry, Weber number, and momentum ratio of the liquid jet to the air crossflow is thoroughly analyzed. Additionally, equations are derived to describe the trajectory for both elliptical and circular nozzles. The relationship between breakup height and breakup length is explored, with the observation that breakup length remains constant for both nozzle shapes. Furthermore, the study delves into the analysis of breakup regimes and establishes a direct correlation between the Weber number and the breakup regime. That column, bag, and Multimode breakup are observed at Weber numbers 4, 38, and 82, respectively. Furthermore, the experimental error for the liquid jet trajectory obtained about 2%. Importantly, the experimental results align with previously published experimental and numerical data, confirming the validity and reliability of the findings.